Time-Varying Compressive Strength Model of Aeolian Sand Concrete considering the Harmful Pore Ratio Variation and Heterogeneous Nucleation Effect - Yugen Li; Huimei Zhang; Xiaoyu Liu; Guangxiu Liu; Dawei Hu; Xiangzhen Meng (Advances in Civil Engineering)
The aim of this study was to analyze the influence mechanism of aeolian sand on the mechanical property of concrete and establish the time-varying compressive strength model. Test studies on the development of concrete’s compressive strength with aeolian sand from the Mu Us Desert were carried out. Influence mechanism of aeolian sand on the strength of concrete was revealed by using the nuclear magnetic resonance (NMR) to analyze the pore ratio and structures of aeolian sand concrete (ASC) and using the X-ray single crystal diffraction (XRD) to calculate the relative contents of hydration products semiquantitatively. Results show that the strength first increases and then decreases with the increase of aeolian sand content, where 20% was the best replacement ratio. With less than 20% content, it promoted the strength by changing the pore structure of concrete and accelerating the cement hydration speed based on its filling effect and chemical activity; when the content was more than 20%, it led to a decrease of strength because of an increase of harmful pore ratio and a weakening of the interface transition zone (ITZ), where the stress concentration and damage when loading are easier to occur. At last, a time-varying compressive strength model of ASC considering the harmful pore ratio variation and heterogeneous nucleation effect was established based on the discussion, published date, and American Concrete Institute (ACI) model, which agrees well with the experimental results and can easily predict the strength of concrete.